Factors associated with anti-retroviral therapy adherence among patients living with HIV during the COVID-19 pandemic: A cross-sectional study - Suryana, Ketut; Suharsono, Hamong; Indrayani, Agung Wiwiek; Wisma Ariani, Luh Nyoman Arya; Putra, Wayan Wahyu Semara; Yaniswari, Ni Made Dwita (Frontiers in Psychiatry, 2022)
Background: COVID-19 Pandemic causes fear and anxiety symptoms on some vulnerable populations included People Living With HIV (PLWH). Physical distancing (when consultation in the clinic) and isolation restrictions will likely have a negative impact / disrupted all care continuum services of HIV disease although health care services and access to ART are continued to operate. Objectives: To investigate the factors associated with adherence to ART among PLWH during COVID-19 pandemic. Methodology: A cross-sectional study was conducted on 324 PLWH who had been on ART for at least 6 months between June 2020 and January 2021. A semi-structured questionnaire was used to interview the participants in order to collect data on sociodemographic characteristics and other factors. Results: A total of 324 PLWH taking ART, 264 (81.48%) were reported with high-adherence (≥95 %), 60 (18.52%) were low-adherence (< 95 %). Factors found to be independently associated with high-adherence to ART were employment status (AOR: 0.030, 95%CI: 0.010-0.088; p < 0.001), type of ARV (AOR: 3.101, 95% CI: 1.137-8.456; p = 0.027), family support (AOR: 0.157, 95% CI: 0.052-0.475; p = 0.001), perception that COVID-19 pandemic negatively impacts ability to come to clinic (AOR: 7.339, 95% CI: 1.46-36.79; p = 0.015), and perception that COVID-19 pandemic negatively impacts ability to take ART (AOR: 10.611, 95%CI: 2.98-37.72; p < 0.001). Conclusions: During the COVID-19 pandemic, the factors associated with high adherence to ART among PLWH who visited to Hospital of Wangaya in Denpasar, Bali, Indonesia were status of employment, ART type (non FDC), family support, and perception that the COVID-19 pandemic negatively impacts ability to come to clinic and ability to take ART.